HOXA5 Derives the Malignant Progression and Cisplatin Resistance of Esophageal Squamous Cell Carcinoma by Regulating USP18‐Mediated IFI27 Deubiquitination - Qiang Wang; Shiheng Ren; Zheng Pan; Yuxin Chen; Xiangyan Liu (Thoracic Cancer)
ABSTRACT Background Chemo‐resistance is a major obstacle to the treatment of esophageal squamous cell carcinoma (ESCC). Interferon alpha‐inducible protein 27 (IFI27) has been reported to be associated with ESCC progression. This study is designed to explore the role and mechanism of IFI27 in the cisplatin (DDP) resistance of ESCC. Methods IFI27 and Ubiquitin‐specific peptidase 18 (USP18) levels were detected by real‐time quantitative polymerase chain reaction (RT‐qPCR). IFI27, multidrug resistance‐associated protein 1 (MRP1), USP18, and Homeobox A5 (HOXA5) protein levels were determined using western blot. DDP resistance, cell viability, proliferation, apoptosis, invasion, and migration were assessed using MTT, EdU, flow cytometry, transwell, and wound healing. Interaction between USP18 and IFI27 was verified using Co‐immunoprecipitation (CoIP) assay. Binding between HOXA5 and USP18 promoter was predicted by JASPAR and validated using Chromatin immunoprecipitation (ChIP) and dual‐luciferase reporter assays. Results IFI27 was upregulated in DDP‐resistant ESCC tissues and cells. IFI27 knockdown repressed DDP resistance, cell proliferation, invasion, migration, and induced cell apoptosis in vitro. Mechanistically, USP18 induced the deubiquitination of IFI27 and prevented its degradation. Furthermore, HOXA5 was a transcription factor of USP18 and activated the transcriptional activity of USP18 via binding to its promoter region. Conclusion USP18 transcriptionally mediated by HOXA5 could promote cell malignant behaviors and DDP resistance through deubiquitinating IFI27, providing a promising therapeutic target for ESCC treatment.